Torsional behavior of precast segment module joints for a submerged floating tunnels. (15th January 2021) - Won, Deokhee; Seo, Jihye; Park, Woo-Sun; Kim, Seungjun
Abstract: In this study, the structural torsional behavior of module joints of steel composite hollow reinforced concrete (RC) for submerged floating tunnels (SFTs) was evaluated experimentally and analytically. The proposed precast model for the SFT had initial stiffness values similar to those of the continuous model. However, the maximum torsional moment of the precast model was lower than that of the continuous model. The torsional moment capacity of the precast model was evaluated by analytical and experimental studies as well as a parametric study. The main parameters included the thickness and connection states of the inner tubes, sizes of the shear keys, and tensile forces of the prestressed concrete (PC) tendons. Among the four parameters, the thickness and connection state of the inner tubes had a more dominant influence. Additionally, the sizes of the shear keys influenced the integration of the concrete parts. During the design of the SFT module joint, these effective parameters should be considered for the improvement of the SFT structural performance. Highlights: This study studied the torsional behavior of module joints with composite hollow RC for the SFT through an experiment and finite element analysis. The main factors for the torsional performance of the precast model were size of shear key, the thickness and connection state of the inner tube. The most effective factors for the torsional performance of the precast model were the thickness and connection state of the inner tube as well as the size of shear keys.